Development and Characterization of Activated Carbon from Olive Pomace: Experimental Design, Kinetic and Equilibrium Studies in Nimesulide Adsorption - Íris Nunes Raupp (MDPI AG, 2021)
The lack of adequate treatment for the removal of pollutants from domestic, hospital and industrial effluents has caused great environmental concern. Therefore, there is a need to develop materials that have the capacity to treat these effluents. This work aims to develop and characterize an activated charcoal from olive pomace, which is an agro-industrial residue, for adsorption of Nimesulide in liquid effluent and to evaluate the adsorption kinetics and equilibrium using experimental design. The raw material was oven dried at 105 °C for 24 h, ground, chemically activated in a ratio of 1:0.8:0.2 of olive pomace, zinc chloride and calcium hydroxide and thermally activated by pyrolysis in a reactor of stainless steel at 550 °C for 30 min. The activated carbon was characterized by Fourier Transform Infrared (FTIR) spectroscopy, X-ray Diffractometry (XRD), Brunauer, Emmett and Teller (BET) method, Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), density and zero charge potential analysis. The surface area obtained was 650.9 m2 g−1. The kinetic and isothermal mathematical models that best described the adsorption were PSO and Freundlich and the highest adsorption capacity obtained was 353.27 mg g−1. The results obtained showed the good performance of activated carbon produced from olive pomace as an adsorbent material and demonstrated great potential for removing emerging contaminants such as Nimesulide.